Campaigns of mass communication and their interface with the public politcs of prevention to the aids in adolescents - Oliveira, Simone HS; Barroso, Maria Grasiela T; Soares, Maria Julia GO (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: due to the relevance of the problematic of the aids for the adolescents the present study was done. Objectives: rescuing and presentingreflections concerning the campaigns of mass communication about prevention of aids among adolescents and its interface with the public politics of preventionof risk to aids and with the promotion of health. Methods: it is a survey carried through in the site of the National Coordination of Prevention of DST and aidsconcerning the campaigns of prevention to the aids in the media. Results: 25 campaigns for preventing aids were released, only three were at the adolescentsand young people. The approaches had been directed for the incentive to the use of the condom by specific groups, without a more specif evaluation of impacts.The cost of the three campaigns was of approximately R 9.000.000,00, emphasizing the lack regularity as well as the lack of a link with actions of educationin health development for promotion of the health of the adolescents. Conclusion: we highlight importance of the strategical propagation of mass communications,mainly television, with regularity, based on studies that show possible ways with respect to more articulated and effective actions and to the proposals ofeducation in health, expropriated by the public politics coming back to this field of activity.